A Circulating Bioreactor Reprograms Cancer Cells Toward a More Mesenchymal Niche. Issue 2 (14th January 2020) - Calamak, Semih; Ermis, Menekse; Sun, Han; Islam, Saiful; Sikora, Michael; Nguyen, Michelle; Hasirci, Vasif; Steinmetz, Lars M.; Demirci, Utkan
Abstract: Cancer is a complex and heterogeneous disease, and cancer cells dynamically interact with the mechanical microenvironment such as hydrostatic pressure, fluid shear, and interstitial flow. These factors play an essential role in cell fate and circulating tumor cell heterogeneity, and can influence the cellular phenotype. In this study, a peristaltic continuous flow reactor is designed and applied to HCT‐116 colorectal carcinoma cells to mimic the fluid dynamics of circulation. With this intervention, a CD44/CD24‐cell subpopulation emerges, and 100 genes are significantly regulated. The expression of cells at 4 h in the flow reactor is very similar to TGF‐ß treatment, which is an inducer of epithelial–mesenchymal transition. ATF3 and SERPINE1 are significantly upregulated in these groups, suggesting that the mesenchymal transition is induced through this signaling pathway. This flow reactor model is satisfactory on its own to reprogram colorectal cancer cells toward a more mesenchymal niche mimicking circulation of the blood. Abstract : This work represents a broadly applicable method to model and predict how colorectal cancer cells respond to hemodynamic continuous flow conditions, which can enable adjusting biological and physical factors under well‐controlled parameters. This flow reactor model can reprogram colorectal cancer cells toward a more mesenchymal niche in circulation, revealing itself as a promising method to mimic fluid dynamics of circulation.